Cookie's fortune - Graham-Barber, Lynda (The Gryphon Press, 2017)
In simple, poetic language, with captivating art that portrays the challenges of a huge city, Cookie's Fortune depicts a stray dog as she searches for food, shelter, and comfort. Compelling and age appropriate, this adorable stray's quest will engage animal-loving children, their parents, teachers, and librarians with its message of hope and compassion. The story is based on the author's own adoption of a dog she saved from a subway station.--Amazon.com